Interpolasi Perlindungan Hak Cipta Berbasis Hak Moral dan Ekonomi Melalui Lisensi di Media Sosial - Aditya Prastian Supriyadi (Badan Strategi Kebijakan Hukum, 2024)
The Constitutional Court's Decision Number 84/PUU-XXI/2023 against Law No. 28 of 2014 emphasizes that Social Media platforms based on User Generated Content are prohibited from being apathetic to copyright infringement on their platforms. However, the Constitutional Court's decision still leaves a legal void in efforts to crack down on social media copyright infringement that is relevant to the copyright protection paradigm. This legal vacuum can cause social media only to act repressively and contradict the copyright protection paradigm, which should include moral and economic aspects to fulfill creators' rights. The article's purpose is to analyze the strengthening of copyright licensing policies. The normative law research method is used as a medium for analyzing issues. The writing approach in this article uses conceptual, comparative, and statute approaches. The study results show that there needs to be a legal construction as the basis for platform licensing policies that are useful for creating proportional interpolation of copyright protection on social media. The platform's active participation greatly protects creators' natural rights from the threat of piracy. According to Personality Theory, creators have moral rights that must be protected to obtain channels of economic rights that can be fulfilled. Implementing this policy is expected to create a more responsible digital ecosystem, provide legal certainty for copyright owners, and ensure fair rewards for their creativity.